2019
DOI: 10.3390/md18010015
|View full text |Cite
|
Sign up to set email alerts
|

Novel Efficient Bioprocessing of Marine Chitins into Active Anticancer Prodigiosin

Abstract: Marine chitins (MC) have been utilized for the production of vast array of bioactive products, including chitooligomers, chitinase, chitosanase, antioxidants, anti-NO, and antidiabetic compounds. The aim of this study is the bioprocessing of MC into a potent anticancer compound, prodigiosin (PG), via microbial fermentation. This bioactive compound was produced by Serratia marcescens TKU011 with the highest yield of 4.62 mg/mL at the optimal conditions of liquid medium with initial pH of 5.65–6.15 containing 1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 42 publications
6
67
0
Order By: Relevance
“…PG has been reported to have effective inhibition against numerous cancerous cell lines, including MCF-7, A549, and Hep G2 in many studies. However, the effect of PG against WiDr has been rarely reported [32]. The result of the biological activities in this study confirmed that the purified PG produced by S. marcescens TNU02 PG was active molecule with potential anticancer properties.…”
Section: Antioxidant and Anticancers Activities Of Purified Pgsupporting
confidence: 80%
See 3 more Smart Citations
“…PG has been reported to have effective inhibition against numerous cancerous cell lines, including MCF-7, A549, and Hep G2 in many studies. However, the effect of PG against WiDr has been rarely reported [32]. The result of the biological activities in this study confirmed that the purified PG produced by S. marcescens TNU02 PG was active molecule with potential anticancer properties.…”
Section: Antioxidant and Anticancers Activities Of Purified Pgsupporting
confidence: 80%
“…Our previous studies revealed that the salt composition, including sulfate and phosphate salts, demonstrate a significant effect on PG production using S. marcescens [11,[30][31][32] (Figure 3).…”
Section: The Effect Of Salt Composition and Some Parameters Of Fermenmentioning
confidence: 93%
See 2 more Smart Citations
“…Chitin and its derivatives have been used in many fields; for instance, environmental treatment, agriculture, medicine, and food [ 4 , 5 , 6 , 7 , 8 ]. Chitinous fishery by-products, such as shrimp heads, shrimp shells, crab shells, and squid pens are the major sources for chitin and chitosan preparations [ 7 , 8 , 9 , 10 , 11 , 12 ]. These types of materials contain a considerable amount of protein [ 13 ].…”
Section: Introductionmentioning
confidence: 99%